Україна в геополітичній доктрині Юрія Липи - Медвідь, Федір Михайлович; Баран, Володимир Васильович (My University, 2013)
З огляду на зростання активності в пошуках Україною фундаментальних напрямків власної геополітичної стратегії, наведено короткий аналіз наріжних основ геополітичної доктрини Юрія Липи. Given the growing activity in Ukraine's search for the fundamental directions of its own geopolitical strategy, a brief analysis of the cornerstones of Yuriy Lypa's geopolitical doctrine is provided.
Keywords: геополітична стратегія; geopolitical strategy; Україна; Ukraine; Липа Юрій; Lypa Yuriу